Urban sustainability in the Arabian Gulf: Air conditioning and its alternatives. (November 2016) - Winter, Tim
This paper examines shifting approaches to urban sustainability in the Arabian Gulf by focusing on the issue of air conditioning and thermal comfort. It considers the recent foregrounding of tradition and heritage within the arena of mega-project development in Qatar, using the Msheireb Downtown Doha Project as an example of a wider regional trend around urban sustainability. Through its focus on air conditioning, the paper draws on Appadurai's recent critique of design singularity to examine built environment sustainability in relation to the indoor comfort norms and practices, for both bodies and objects, which are now well established across the Gulf region.